HUBUNGAN PERSEPSI FASILITAS BELAJAR DI SEKOLAH DAN KEAKTIFAN BELAJAR DENGAN PRESTASI BELAJAR PADA MATA PELAJARAN DASAR TEKNIK MESIN DI SMK NEGERI 1 WOHA TAHUN AJARAN 2020/2021 - FADLURRAHMAN RAHMAN; Samidjo; Dianna Ratnawati (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2024)
The purpose of this research was to see: (1) the relationship between perceptions of learning facilities in schools with learning achievement in the basic subject of mechanical engineering; (2) the relationship between active learning and learning achievement in the basic subject of mechanical engineering; and (3) the relationship between perceptions of learning facilities in schools and active learning with student achievement in the basic subject of mechanical engineering. This research is an ex-post facto research. The data collection was carried out through a questionnaire and documentation method. In this study, the population was all students of class X Mechanical Engineering SMK N 1 Woha totaling 30 students. Testing the validity and reliability of the instrument was carried out with the help of SPSS 21 for windows. The prerequisite tests used include the normality test, linearity test and multicollinearity test. In analyzing the data using the Pearson Product Moment correlation analysis technique for H1 and H2 and multiple correlation analysis for H3. The results of the study show that: (1) there is a significant positive relationship between perceptions of learning facilities in schools and learning achievement in basic mechanical engineering; (2) there is a significant positive relationship between learning activity and learning achievement in basic mechanical engineering; (3) there is a significant positive relationship between perceptions of learning facilities in schools and active learning with learning achievement in basic mechanical engineering.